Monitoring the impact of COVID-19 in Myanmar: Rice millers – January 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand how Myanmar’s rice value chain has been affected by the COVID-19 crisis, a series of telephone interviews is being conducted with more than 400 rice millers from Ayeyarwady, Bago, and Yangon. This report presents data from interviews conducted in January 2021.